Data-Driven Journalism Media - Putra, Richo Kesatria Eka (Jurnal Mahardika Adiwidia, 2023)
Research with the title data-driven journalism this Tempo aims to find out why and how to digitize media used in data journalism on data-driven Journalism Tempo. This research uses qualitative methods and uses new media theory, mediamorphosis theory, and the concept of journalism data to analyze research and achieve these goals. The results of this study show Tempo applies data journalism in its investigations in order to assert differentiation; in line with their vision of media digitization, and in order to maximize the end result of the content. The application of media digitization and data journalism also influences the adjustment of thinking patterns in the ranks of the public editor. The conclusion of this research is that Tempo has a vision for the process of media digitization that they do. The existence of data-driven journalism is in line with Tempo's digitalization vision. This is confirmed by the presence of an application that offers creative space for data-based investigative content. The application can become Tempo's support in attracting a number of millennial generation readers for the sake of supporting the sustainability of the media.